Clinical performance evaluation of the Idylla™ EGFR Mutation Test on formalin-fixed paraffin-embedded tissue of non-small cell lung cancer - Mercedes Delgado-García; Birgit Weynand; Lourdes Gómez-Izquierdo; María José Hernández; Ángela María Blanco; Mar Varela; Xavier Matias-Guiu; Ernest Nadal; Bélgica Márquez-Lobo; Ana Alarcão; Enrique de Álava; Michele Biscuola (BMC Cancer, 2020)
Abstract Background Detection of epidermal growth factor receptor (EGFR) mutations in exons 18–21 is recommended in all patients with advanced Non-small-cell lung carcinoma due to the demonstrated efficiency of the standard therapy with tyrosine kinase inhibitors in EGFR-mutated patients. Therefore, choosing a suitable technique to test EGFR mutational status is crucial to warrant a valid result in a short turnaround time using the lowest possible amount of tissue material. The Idylla™ EGFR Mutation Test is a simple, fast and reliable method designed for the detection of EGFR mutations from formalin-fixed paraffin-embedded samples. The aim of this study was the Clinical Performace Evaluation of the Idylla™ EGFR Mutation Test on the Idylla™ System. Methods EGFR mutational status was determined on 132 archived formalin-fixed paraffin-embedded tissue sections with Idylla™ technology. Results were compared with the results previously obtained by routine method in the reference lab (Therascreen® EGFR RGQ PCR v2, Qiagen in Molecular Pathology lab, Hospital Universitario Virgen del Rocío de Sevilla). Results The overall agreement between results obtained with the Idylla™ EGFR Mutation Test and the Comparator test method was 95.38% (with 1-sided 95% lower limit of 91.7%) showing Positive Diagnostic Agreement of 93.22% and Negative Diagnostic Agreement of 97.18%, with a Limit Of Detection ≤5%. Conclusions The Idylla™ EGFR Mutation Test passed its clinical validity performance characteristics for accuracy.